Factors influencing infant Feeding Method in an Urban Community - Rose, Vivienne A; Warrington, Verlyn O F; Linder, Roland; Williams, Connie S (Journal of the National Medical Association, 2004)
The benefits of breastfeeding are well established. However, despite this fact, rates of breastfeeding continue to be low, falling far below the goals of Healthy People 2010. Rates are even lower among ethnic minority and low-income women. In this study, we attempt to identify the factors that most influence a mother's choice of infant feeding method in an urban predominately African-American population. Phone interviews of 70 women who delivered full-term infants at an urban tertiary care hospital were conducted in order to explore knowledge, attitudes, and beliefs about breastfeeding of the mothers and that of members of their social support network. Ten mothers (14%) exclusively breastfed. Older, caucasian, and married women were more likely to breastfeed. Breastfeeding mothers reported more partner support as well as more family knowledge about breastfeeding and had more positive attitudes about breastfeeding. Healthcare providers were not directly influential in mother's feeding choice. From this study, we conclude that in this population, the mother's partner and family are most influential in the choice of infant feeding method and, thus, should be included in breastfeeding promotion programs.
Keywords: Adolescent; Adult; Attitude; Baltimore; Bottle Feeding; Breast Feeding; Female; Humans; Social Support; Urban Population